Public service as a policy in the field of fundamental rights: implications - Arrúa Gobo, Miguel Angel (Universidad Nacional del Litoral, 2018)
One of the legal constructions that has had the most evolution, conceptual and content divergences, has been and is that of the Public Service, mainly because of its particular inclusion in the theories about the State but also because of its scope as a guarantee tool for human rights. , given the evolution of Administrative Law and the generation of regulatory convergence spaces that require answers different from those tested in the last century. This article will briefly address the transformation of the notion of Public Service from the perspective of fundamental rights, its inclusion in typologies elaborated by the doctrine and the implications of a schematization that, under the influence of conventional developments that are part of the block of existing juridicity and doctrinaire interpretation, decant in a proposal closely related to the application -in this field- of the principle of joint action as a guarantee technique of the prerogatives committed in the analyzed figure, being here a fertile ground for the development of such precept.